Integration of Ship Machinery Maintenance and Control Systems in Maritime Education: Enhancing Industry Readiness - R.Herlan Guntoro; Pargaulan Dwikora Simanjuntak (Journal Of Business, Finance, and Economics (JBFE), 2024)
This research investigates ship machinery maintenance and control systems within maritime transportation vocational schools, focusing on integrating practical experiences and stakeholder perspectives. Qualitative data from maritime professionals, educators, and senior cadets highlight the importance of predictive maintenance strategies and advanced technologies such as IoT and AI in enhancing operational efficiency and reducing costs. The study identifies a skills gap among professionals, emphasising the need for continuous training to bridge this divide. Longitudinal internship analysis reveals significant skill development and practical knowledge acquisition among senior cadets, underscoring the effectiveness of experiential learning in vocational education. Furthermore, a transdisciplinary approach elucidates trends in sustainability integration, promoting eco-friendly practices and economic resilience within maritime operations. The findings advocate for curriculum updates that align with industry demands, preparing graduates for sustainable and competitive careers in the evolving maritime sector.